(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article, the author considers the role and importance of information technology and digitalization in local governments. The authors noted that new technologies change not only the ways of producing products and services, but also create new opportunities for the realization of civil rights, self-realization of the individual, gaining knowledge, educating a new generation and spending leisure time. Distances are shrinking in the information society, globalization is taking place, and unprecedented opportunities are being created for the development of regions.